How to Define? Towards a Comparative Definition of Central Asia as a Modern International Region - Pierre Chabal (Ukrainian Policymaker, 2025)
Does a (regional) phenomenon occur because another phenomenon (crisis) occurs, therefore in causal relation to the latter? Or does this phenomenon (multi-regionalization) occur when a new context arises, where old imperatives (of conflict regulation) fit into new mechanisms (inter-sovereign ones)? This ‘insertion’ occurs as much elsewhere, in another space, as in such or such a region of the world, therefore without a causal (determining) relation with any one of these regions in particular. The question of specificity establishes the link between the methodology of analysis and the epistemology of explanation. In this spirit, one seeks to establish a ‘context’ of ‘determination.’ Going into generality from regional cases sheds light on the modern regional phenomenon in Central Asia: not as specific but as common, contributing to avoid the trap of a sui generis specificity.